As(V) removal from aqueous solutions by coagulation with liquid phase of red mud - Altundoğan, Hamdi Soner; Tümen, Fikret (My University, 2003)
As(V) removal by using liquid phase of red mud (LPRM) is reported in this article. The experimental section includes characterization of LPRM, as well as As(V) removal from arsenical aqueous solution mixed with LPRM by coagulation in the column. As(V) removal study was divided into two parts; neutralization of LPRM-arsenical solution mixtures with acid solution accompanied with air-agitation and neutralization of those mixtures with CO2 gas. Effect of LPRM/(As(V) solution) volumetric ratio on the removal of As(V) by co-precipitation arsenic together with aluminum present as aluminate in the LPRM were studied. Al/As(V) molar ratio values on the removal of As(V) is evaluated. Results show that As(V) was removed effectively by LPRM with a volumetric LPRM/(As(V) solution) ratio of 0.1 from an arsenical solution in the As(V) concentration of 20 mg dm?3. For an efficient removal, it was found to be required an Al/As(V) molar ratio of 6–8. The results suggest that it is advantageous to use a waste material of red mud liquid phase in the treatment of arsenical wastewater, possibly conjunction with red mud solids as adsorbent that its adsorption ability has been demonstrated earlier.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: As(V) removal; Coagulation; Red mud; Bayer process residue